2001
DOI: 10.1103/physrevb.64.153305
|View full text |Cite
|
Sign up to set email alerts
|

Fermi-liquid theory for the Anderson model out of equilibrium

Abstract: The low-energy properties of the Anderson impurity are studied under a finite bias voltage V using the perturbation theory in U of Yamada and Yosida in the nonequilibrium Keldysh diagrammatic formalism. The self-energy is calculated exactly up to terms of order ω 2 , T 2 and V 2 using Ward identities. The coefficients are defined with respect to the equilibrium ground state, and contain all contributions of the perturbation series. From these results, the nonlinear response of the current through the impurity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
162
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(175 citation statements)
references
References 19 publications
13
162
0
Order By: Relevance
“…For this purpose we use an asymptotic expression for in the low energy, low bias voltage and low temperature, 24) …”
Section: Zero Magnetic Field 511 Currentmentioning
confidence: 99%
“…For this purpose we use an asymptotic expression for in the low energy, low bias voltage and low temperature, 24) …”
Section: Zero Magnetic Field 511 Currentmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35] We have shown that the Keldysh Green's function 36,37 is solvable in the opposite limit eV → ∞, where the excitations of whole energy scales equally contribute to the dynamics. In this limit, the model can be mapped onto a nonHermitian Hamiltonian of two effective sites in a doubled Hilbert space that is defined in the thermal field theory.…”
Section: -12mentioning
confidence: 99%
“…The application along this line seems to be interesting in relation to the metal-insulator transition observed in two-dimensional systems. 28) Furthermore, extensions to the finite temperatures 29) and nonequilibrium situations 30) are left for future studies.…”
Section: Remarksmentioning
confidence: 99%